Universal Automobile Headlight Control Module for High Beam Adaptation during Night Vision Travel an Embedded Design Approach - M. Subramania Siva; G. Jeyakumar (Institute of Advanced Engineering and Science, 2018)
Road accidents during night travel increases day by day and vision impairment due to high beam contributes to the majority of the total fatalities. Headlights of vehicles pose a great danger during night driving. [1] The drivers of most vehicles use high/bright beam while driving at night. This causes a discomfort to the person travelling from the opposite direction. The driver experiences a sudden glare caused due to the high intense headlight beam from the other vehicle coming towards him from the opposite direction. We are expected to dim the headlight to avoid this glare. This glare causes a temporary blindness to a person resulting in road accidents during the night. To avoid such incidents, an embedded prototype of Automatic Headlight adaptor module is proposed. This embedded module automatically switches the high beam to low beam and returns backs to high beam, thus reducing the sudden glare effect. It also eliminates the requirement of manual switching by the driver to switch back to low beam Universal Headlight adaptor module is a unique solution to achieve the above objective, the headlight intensity of the incoming vehicles causing the glare is automatically attenuated to low beam wirelessly by the nearby vehicles affected by high beam. The interconnected modules at every vehicle independently takes the decision on the head light control of the source vehicle causing the glare by evaluating various parameters like vehicle speed, current GPS location, direction of vehicle etc.